1983
DOI: 10.1136/jmg.20.5.394
|View full text |Cite
|
Sign up to set email alerts
|

Complete trisomy 5p owing to de novo translocation t(5;22)(q11;p11) with isochromosome 5p associated with a familial pericentric inversion of chromosome 2, inv 2(p21q11).

Abstract: Case reports a karyotype of 46,X,del(Y)(ql 1). The deleted Y had neither C positive nor brightly fluorescing bands ( figure). The Y chromosome of the proband's father was normal in appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…Previous reports have suggested that the larger the duplicated portion of 5p the greater the number and severity of physical abnormalities (Khodr et al 1982, Leschot & Lim 1979, Orye et al 1983, Zabel et al 1978. The observations reported here, where only mild effects resulted from duplication of what in our interpretation involved more than five eighths of the length of 5p.…”
Section: Discussionsupporting
confidence: 50%
“…Previous reports have suggested that the larger the duplicated portion of 5p the greater the number and severity of physical abnormalities (Khodr et al 1982, Leschot & Lim 1979, Orye et al 1983, Zabel et al 1978. The observations reported here, where only mild effects resulted from duplication of what in our interpretation involved more than five eighths of the length of 5p.…”
Section: Discussionsupporting
confidence: 50%
“…Our patient has had no seizures and an EEG was not performed. All patients reported, except ours and that of Chen et al [1995], had apparently low-set "dysplastic" ears, while our patient had only a unilateral shallow preauricular *Patients with duplications affecting at least part of band 5p13 and part of bands 5p14-5p15: 1- Brimblecombe et al, 1977;2-Zabel et al, 1978;3-Vowles et al, 1984;4-Kleczkowska et al, 1987;5-Gustavson et al, 1988;6-Rethore' et al, 1989;7-Leichtman et al, 1991;8-Chen et al, 1995;9-Lorda-Sanchez et al, 1997. a Complete dup 5p: number of cases who presented these features out of the following six cases: Leshot and Lim, 1979;Kunze et al, 1980;Carnevale et al, 1982;Orye et al, 1983;Fujita et al, 1994;Zhao et al, 1995. Old cases without GTG bands and those with other possible aberrations in the implicated chromosomes have not been included. Laryngeal cleft, renal pelvic enlargement vesico-uretero-junction reflux, first degree hypospadias, and cryptorchidism were only reported in the patient of Leichtman et al, 1991. pit.…”
Section: Discussionmentioning
confidence: 97%
“…Both partial and complete duplication of the chromosome 5p are known. Partial trisomy often results from a parental translocation or inversion [Reichenbach et al, 1999], whereas complete trisomy has been described in patients with isochromosome 5p and translocation of the long arm of the same chromosome to the end of another chromosome [Leschot and Lim, 1979;Orye et al, 1983;Fujita et al, 1994]. Furthermore, complete trisomy 5p was found in patients with translocation of the whole 5p onto the short arm of an acrocentric chromosome [Carnevale et al, 1982;Zhao et al, 1995;Brimblecombe et al, 1997] or present as a supernumerary chromosomal marker [Reichenbach et al, 1999].…”
Section: Introductionmentioning
confidence: 95%